Tunable photonic structures based on silicon and liquid crystals - Tolmachev, V. A.; Astrova, E. V.; PEROVA, TANIA (My University, 2008)
This paper is focused on the design, fabrication and characterization of the conventional and tunable photonic devices based on grooved silicon, serving as one-dimensional (1D) photonic crystal. The advantages of these photonic structures are as follows: the large refractive index contrast, in-plane moulding of the light flow, the possibility to fabricate a composite photonic structures by filling the grooves with a different compounds and compatibility with current semiconductor processing techniques. The optical properties of grooved Si structures were simulated using a transfer matrix method and gap map method and have been verified experimentally using FTIR microscopy. The air spaces in the basic silicon-air matrices were infiltrated with nematic liquid crystal E7. It is shown that the optical properties of the obtained composite 1D photonic crystals can be tuned by means of electro- and thermo-optical effects. Such a structures suit well for the various elements of the integrated optics and can serve as a building blocks for optical interconnects.
PUBLISHED
Keywords: tunable photonic devices; silicon microphotonics